Piranhas - Chancellor, Deborah (Mankato, Minn. Smart Apple Media, 2009)
"Advice for kids on how to choose and care for several common breeds of piranhas, including tank setup, feeding, and keeping piranhas healthy"--Provided by publisher.
What Are Piranhas? 4 -- Red-Bellied Piranhas 6 -- Black, Red-Throated, and Pike Piranhas 8 -- Keeping Piranhas 10 -- Choosing the Right Tank 12 -- Heaters and Filters 14 -- Decorations and Lighting 16 -- Setting up Your Aquarium 18 -- Buying Your Piranhas 20 -- Feeding Your Piranhas 22 -- Cleaning Your Tank 24 -- Keeping Healthy Piranhas 26 -- Caring for Your Aquarium 28.
"A+."
Includes index.
8 - 12 years
Keywords: Piranhas; Juvenile works